2019
DOI: 10.22392/actaquatr.577155
|View full text |Cite
|
Sign up to set email alerts
|

Maritime Jurisdiction Areas and Fisheries Activities of Riparian Countries in the Black Sea

Abstract: Bu çalışmada, Karadeniz'e kıyısı olan Türkiye, Gürcistan, Rusya Federasyonu, Ukrayna, Romanya ve Bulgaristan'ın balıkçılık sahalarının ve av güçlerinin büyüklüğü tespit edilmiş, 1950 yılından itibaren kıyıdaş ülkelerin bu denizden avladıkları su ürünlerinin miktarları incelenmiştir. Av ve av gücü verileri "www.seaaroundus.org" ve FAO balıkçılık istatistiklerinden alınmıştır. Bunun yanı sıra ülkelerin resmi istatistikleri ve yapılan bilimsel araştırmaların sonuçlarından da yararlanılmıştır. Kıyıdaş ülkelerin Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Our research has revealed that the whiting in the south-eastern coasts of the Black Sea is fed almost exclusively with small individuals of its own species (whiting) and other small-bodied fish species (horse mackerel, anchovy, sprat, and rockfish). Especially the decrease of anchovy in the last 25 years and sprat in the last 10 years (Balık, 2019) has negatively affected the feeding of whiting in the south-eastern Black Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Our research has revealed that the whiting in the south-eastern coasts of the Black Sea is fed almost exclusively with small individuals of its own species (whiting) and other small-bodied fish species (horse mackerel, anchovy, sprat, and rockfish). Especially the decrease of anchovy in the last 25 years and sprat in the last 10 years (Balık, 2019) has negatively affected the feeding of whiting in the south-eastern Black Sea.…”
Section: Discussionmentioning
confidence: 99%